Tsetse fly distribution and occurrence of Trypanosoma species among cattle and goats around Queen Elizabeth National park, Uganda - Adiukwu, Paul Chukwuemeka; Bonsu, Martina; Okon-Ben, Inemesit; Peprah, Paul; Mensah-Kane, Paapa; Jato, Jonathan; Nambatya, Grace (International Journal of Biological and Chemical Sciences, 2017)
The use of herbal therapy is a common practice in Africa. One of the commonly used herbs is Vernonia amygdalina. Processing of the plant for use leads to the loss of phytochemical principles like saponin which has been shown to possess bioactivity. This study was to evaluate and characterize the saponin principles, using chromatographic and spectroscopic techniques. Standard antipyretic study procedure using Saccharomyces cerevisiae induced pyrexia in rats was used for the evaluation of the herbal aqueous extract, as well as, the crude saponin and its chromatographic fraction. The separation and chromatogram development of resulting pure saponin components was carried out using a HPLC with UV-vis detection at 365 nm. Data for the antipyretic study agrees with previous bioactivity report for the saponin. Chromatographic and spectroscopic evaluation indicated the presence of three pure saponin components at retention times of 7.78 ± 0.19, 8.76 ± 0.16 and 13.54 ± 0.87 minutes, in the fractionate. Finding suggests that the pure components are individual or collective contributors to the bioactivity of the crude saponin and fractionate. Further bioactivity probe of the pure components will aid good understanding and use of the herbal medication.
Keywords: Chromatographic, detection, pure components, bioactivity, rats